Unusual Oxidative Dealkylation Strategy Toward Functionalized Phenalenones as Singlet Oxygen Photosensitizers and Photophysical Studies - Sandoval-Altamirano, C (American Chemical Society, 2020)
A series of functionalized 6-alkoxy phenalenones was prepared through an unprecedented oxidative dealkylation of readily available phenalene precursors. The starting phenalenes were efficiently synthesized via an aminocatalyzed annulation/O-alkylation strategy starting from simple substrates. The spectroscopic properties of some phenalenones were investigated in different solvents. Introducing an alkoxy substituent at the 6-position onto the phenalenone framework results in a red shift of the absorption. The synthesized phenalenones exhibit low fluorescence quantum yields, and the fluorescence decay was studied in different solvents, highlighting the presence of several lifetimes. The singlet oxygen (1O2) photosensitizing propensity of some phenalenones was investigated, and the results showed the striking importance of the phenalenone molecular structure in generating singlet oxygen with high yields. The ability of phenalenones to generate singlet oxygen was then harnessed in three photooxygenation reactions: Anthracene oxidation, oxy-functionalization of citronellol through the Schenck-ene reaction, and photooxidation of a diene. Copyright © 2020 American Chemical Society.